Iliad: Moving Medical Decision-Making into New Frontiers - Warner, H. R., Jr. (Methods of Information in Medicine, 1989)
If the essence of clinical practice is a process of sequential problem-solving, whereby a physician works with a patient to formulate a series of decisions about diagnostic treatment, then it would naturally follow that the essence of medical education should evolve around the training of would-be clinicians in the difficult art of diagnostic decisionmaking. Yet this is not often the case.
Keywords: Decision Support Systems; Computer-Assisted Diagnosis; Computer-Based Problem Solving; Expert Systems; Computer Simulation